Chinese herbal medicine for threatened miscarriage: An updated systematic review and meta-analysis - Xie, Hongliang; Zhang, Aolin; Mou, Xuan; He, Tao; Li, Junwei; Wang, Chi Chiu; Fan, Xiaohui; Li, Lu (Frontiers in Pharmacology, 2023)
Objective: To conduct an updated systematic review and meta-analysis on the efficacy and safety of Chinese herbal medicine (CHM) for threatened miscarriage. Data Sources: Electronic databases were searched from inception to 30 June 2022. Study Eligibility Criteria: Only randomized controlled trials (RCTs) that assessed the efficacy and safety of CHM or combined CHM and Western medicine (CHM-WM) and compared with other treatments for threatened miscarriage were included for analysis. Methods: Three review authors independently evaluated included studies, assessed the risk of bias and extracted data for meta-analysis (continuation of pregnancy after 28 gestational weeks, continuation of pregnancy after treatment, preterm birth, adverse maternal outcomes, neonatal death, TCM syndrome severity, β-hCG levels after treatment), sensitivity analysis (β-hCG level) and subgroup analysis (TCM syndrome severity, β-hCG level). The risk ratio and 95% confidence interval were calculated by RevMan. Certainty of the evidence was assessed according to GRADE. Results: Overall, 57 RCTs involving 5,881 patients met the inclusion criteria. Compared with WM alone, CHM alone showed significant higher incidence of continuation of pregnancy after 28 gestational weeks (Risk Ratio (RR) 1.11; 95% CI 1.02 to 1.21; n = 1; moderate quality of evidence), continuation of pregnancy after treatment (RR 1.30; 95% CI 1.21 to 1.38; n = 10; moderate quality of evidence), higher β-hCG level (Standardized Mean Difference (SMD) 6.88; 95% CI 1.74 to 12.03; n = 4) and lower Traditional Chinese medicine (TCM) syndrome severity (SMD −2.94; 95% CI −4.27 to −1.61; n = 2). Compared with WM alone, combined CHM-WM showed significant higher incidence of continuation of pregnancy after 28 gestational weeks (RR 1.21; 95% CI 1.16 to 1.27; n = 15; moderate quality of evidence), continuation of pregnancy after treatment (RR 1.19; 95% CI 1.16 to 1.23; n = 41; moderate quality of evidence), higher β-hCG level (SMD 2.27; 95% CI 1.72 to 2.83; n = 37) and lower TCM syndrome severity (SMD −1.74; 95% CI −2.21 to −1.27; n = 15). No significant differences in reducing the adverse maternal outcomes and neonatal death were found in combined CHM-WM compared with WM alone (RR 0.97; 95% CI 0.62 to 1.52; n = 8; RR 0.39; 95% CI 0.12 to 1.21; n = 2). Conclusion: Current evidence supported CHM could be a potential treatment for threatened miscarriage. However, results should be interpreted with caution considering the low to moderate quality of the available evidence. Systematic Review Registration: [https://inplasy.com/inplasy-2022-6-0107/], identifier [INPLASY20220107].